CARPOSEMINAL BIOMETRY AND GERMINATION OF Cabralea canjerana (Vell.) Mart. - Rickli-Horst, Helena Cristina; Duarte, Manoela Mendes; Chirinzane, Cacilda João; Nogueira, Antonio Carlos (Floresta, 2017)
Cabralea canjerana is a species that has ecological and economic importance for the Southern Brazil. This study aimed to characterize the biometry of fruits and seeds as well as the C. canjerana germinative process submitted to different substrates and temperatures. The biometric characteristics of fruits and seeds were analyzed with the aid of digital caliper. In the germination test, the substrates blotting paper, sand and vermiculite, and the temperatures of 20, 25 and 30 ºC were used. The germination percentage, mean germination rate (MGR), mean germination time (MGT), synchronization index (SI), fresh mass (FS) and dry mass (DM) of seedlings were assessed. The highest germination percentages occurred for vermiculite at three temperatures, blotting paper at 25 °C and sand at 20 and 30 °C. There was seedling formation in all treatments. The use of the sand substrate and the temperatures of 25 and 30 °C provided lower mean values of MGT and SI and higher mean values of MGR. The highest DM occurred with sand at the temperature of 20 ºC. The biometric characteristics of fruits and seeds varied. We recommend the use of vermiculite at temperatures of 20, 25 and 30 ºC, blotting paper at 25 °C and sand at 20 and 30 °C for germination tests. Keywords: Meliaceae, native species, germination potential, temperature, substrate. Resumo: Biometria carpo seminal e germinação de Cabralea canjerana (Vell.) Mart. Cabralea canjerana é uma espécie que possui importância ecológica e econômica para o Sul do Brasil. Este estudo objetivou caracterizar a biometria de frutos e sementes, assim como o processo germinativo de C. canjerana submetido a diferentes substratos e temperaturas. Analisaram-se as características biométricas de frutos e sementes com auxílio de paquímetro digital. No teste de germinação, foram utilizados os substratos papel mata-borrão, areia e vermiculita e as temperaturas de 20, 25 e 30 ºC, avaliando-se a porcentagem de germinação, velocidade média de germinação (VMG), tempo médio de germinação (TMG), índice de sincronização (I), massa fresca (MF) e massa seca (MS) de plântulas. As maiores porcentagens de germinação ocorreram com vermiculita nas três temperaturas, papel mata-borrão a 25 °C e areia a 20 e 30 °C. Houve formação de plântulas em todos os tratamentos. O uso do substrato areia e das temperaturas de 25 e 30 ºC proporcionou menores médias de TMG e I e maiores médias de VMG. A maior MS ocorreu utilizando-se areia sob temperatura de 20 ºC. Ocorreu variação das características biométricas de frutos e sementes. Recomenda-se a utilização de vermiculita nas temperaturas de 20, 25 e 30 ºC, papel mata-borrão a 25 °C e areia a 20 e 30 °C para testes de germinação. Palavras-chave: Meliaceae, espécie nativa, potencial germinativo, temperatura, substrato.